Arenavirus Budding - Urata, Shuzo (Hindawi Publishing Corporation, 2011)
Several arenaviruses cause hemorrhagic fever disease in humans and pose a significant public health concern in their endemic regions. On the other hand, the prototypic arenavirus LCMV is a superb workhorse for the investigation of virus-host interactions and associated disease. The arenavirus small RING finger protein called Z has been shown to be the main driving force of virus budding. The budding activity of Z is mediated by late (L) domain motifs, PT/SAP, and PPXY, located at the C-terminus of Z. This paper will present the current knowledge on arenavirus budding including the diversity of L domain motifs used by different arenaviruses. We will also discuss how improved knowledge of arenavirus budding may facilitate the development of novel antiviral strategies to combat human pathogenic arenaviruses.